Novinky v lécení nespecifických strevních zánĕtů - Maratka, Z (Vnitrni lekarstvi, 1993)
This term comprises idiopathic proctocolitis (IPC) and regional enteritis (RE, Crohn's disease). Despite a number of similarities (similar age, symptoms, immunology, drugs), the two conditions differ substantially (site, pathology, surgery) and thus from a practical aspect it is essential to differentiate them. The term "ulcerative colitis" comprises also other inflammations, e.g. recently identified infections with causal agents which are difficult to diagnose. There are also several types of regional enteritis which differ as to their course and sequelae. As regards medical treatment, in both conditions in particular corticosteroids are used and 5-aminosalicylic acid. An important novelty are 5-aminosalicylic acid tablets with prolonged action; different types are used depending on the site of the disease. Surgical treatment differs not only as to its frequency but also by the type of operation. In regional enteritis operations confined to the affected site are used, while in idiopathic proctocolitis standard operations are available: proctocolectomy, colectomy with an ileorectal anastomosis, with continent ileostomy or with an ileoanal anastomosis and reservoir. The latter is preferred nowadays.
Keywords: Inflammatory Bowel Diseases; Humans; lidé; idiopatické střevní záněty